The mitten : a Ukrainian folktale - Brett, Jan, 1949- (New York : G.P. Putnam's Sons, 2009)
Several animals sleep snugly in Nicki's lost mitten until the bear sneezes.
3.5
K-3
Keywords: Folklore -- Ukraine; Mittens -- Folklore; Folklore -- Ukraine; Mittens -- Folklore; Folklore -- Ukraine; Mittens -- Folklore; Picture books for children